Fusion of technological objectivity into the underlying anarchy of elite snowboarding: insight from the Australian national snowboard coach - Harding, J. W.; James, D. A. (Sports Technology, 2008)
It seems there is definite potential for automated objectivity to provide assistance to snowboard athletes and coaches striving to enhance athletic performance and to judges in their quest to accurately and reliably assess competition performance. It is, however, imperative that integration of any such technological innovation into the sporting discipline of half-pipe snowboarding be conducted alongside key practice community members in order to ensure that the sport retains whatis currently valued: its capacity to provide a platform that allows competitive individuality and athletic freedom of expression. The complete interview can be listened to at www.AnarchistAthlete.com